Increased Access to and Use of Endovascular Therapy Following Implementation of a 2-Tiered Regional Stroke System. Issue 3 (March 2020) - Bosson, Nichole; Gausche-Hill, Marianne; Saver, Jeffrey L; Sanossian, Nerses; Tadeo, Richard; Clare, Christine; Perez, Lorrie; Williams, Michelle; Rasnake, Sara; Nguyen, Phuong-Lan; Taqui, Asif; Evans-Cobb, Cheryl; et al.
Abstract : Background and Purpose—: We quantified population access to endovascular-capable centers, timing, and rates of thrombectomy in Los Angeles County before and after implementing 2-tiered routing in a regional stroke system of care. Methods—: In 2018, the Los Angeles County Emergency Medical Services Agency implemented transport of patients with suspected large vessel occlusions identified by Los Angeles Motor Scale ≥4 directly to designated endovascular-capable centers. We calculated population access to a designated endovascular-capable center within 30 minutes comparing 2016, before 2-tiered system planning began, to 2018 after implementation. We analyzed data from stroke centers in the region from 1 year before and after implementation to delineate changes in rates and speed of administration of tPA (tissue-type plasminogen activator) and thrombectomy and frequency of interfacility transfer. Results—: With implementation of the 2-tier system, certified endovascular-capable hospitals increased from 4 to 19 centers, and within 30-minute access to endovascular care for the public in Los Angeles County, from 40% in 2016 to 93% in 2018. Comparing Emergency Medical Services–transported stroke patients in the first post-implementation year (N=3303) with those transported in the last pre-implementation year (N=3008), age, sex, and presenting deficit severity were similar. The frequency of thrombolytic therapy increased from 23.8% to 26.9% (odds ratio, 1.2 [95% CI, 1.05–1.3]; P =0.006), and median first medical contact by paramedic-to-needle time decreased by 3 minutes ([95% CI, 0–5] P =0.03). The frequency of thrombectomy increased from 6.8% to 15.1% (odds ratio, 2.4 [95% CI, 2.0–2.9]; P <0.0001), although first medical contact-to-puncture time did not change significantly, median decrease of 8 minutes ([95% CI, −4 to 20] P =0.2). The frequency of interfacility transfers declined from 3.2% to 1.0% (odds ratio, 0.3 [95% CI, 0.2–0.5]; P <0.0001). Conclusions—: After implementation of 2-tiered stroke routing in the most populous US county, thrombectomy access increased to 93% of the population, and the frequency of thrombectomy more than doubled, whereas interfacility transfers declined.